Comparison of three clinical scoring tools for bronchiolitis to predict the need for respiratory support and length of stay in neonates and infants up to three months of age - De Rose, Domenico Umberto; Maddaloni, Chiara; Martini, Ludovica; Braguglia, Annabella; Dotta, Andrea; Auriti, Cinzia (Frontiers in Pediatrics, 2023)
Background Bronchiolitis severity can be assessed using different clinical scores. Some of the most used are the Wang Bronchiolitis Severity Score (WBSS), the Kristjansson Respiratory Score (KRS), and the Global Respiratory Severity Score (GRSS), calculated on the vital parameters and the clinical conditions. Objective To assess which of the three clinical scores better predicts the need for respiratory support and length of hospital stay in neonates and infants younger than three months, admitted to neonatal units for bronchiolitis. Methods Neonates and infants younger than three months admitted to neonatal units from October 2021 to March 2022 were included in this retrospective study. The scores were calculated in all patients soon after admission. Results Ninety-six patients (of whom 61 neonates) admitted for bronchiolitis were included in the analysis. Median WBSS at admission was 4.00 (interquartile range, IQR 3.00–6.00), median KRS was 4.00 (IQR 3.00–5.00), and median GRSS 4.90 (IQR 3.89–6.10). We found significant differences in all three scores between infants who needed respiratory support (72.9%) and those who did not (27.1%) (p < 0.001). A value >3 for WBSS, > 3 for KRS, and >3.8 for GRSS were accurate in predicting the need for respiratory support, with a sensitivity of 85.71%, 75.71%, and 93.75% and a specificity of 80.77%, 92.31%, and 88.24%, respectively. The three infants who required mechanical ventilation had a median WBSS of 6.00 (IQR 5.00–6.50), a KRS of 7.00 (IQR 5.00–7.00), and a GRSS of 7.38 (IQR 5.59–7.39). The median length of stay was 5 days (IQR 4–8). All three scores were significantly correlated with the length of stay, although with a low correlation coefficient: WBSS with an r2 of 0.139 (p < 0.001), KRS with an r2 of 0.137 (p < 0.001), and GRSS with an r2 of 0.170 (p < 0.001). Conclusion Clinical scores WBSS, KRS, and GRSS calculated on admission accurately predict the need for respiratory support and the length of hospital stay in neonates and infants younger than three months with bronchiolitis. The GRSS score seems to better discriminate the need for respiratory support than the others.